Intelligent computing theories and methodologies : 11th International Conference, ICIC 2015, Fuzhou, China, August 20-23, 2015 : proceedings /: 11th International Conference, ICIC 2015, Fuzhou, China, August 20-23, 2015 : proceedings. ([2015]) - Unknown
No abstract available